(untitled) (Journal of Architectural Design, 2021)
This article discusses the requirements for modern water devices, modern trends in the design and construction of water devices, measures for the efficient use of water in the design of water devices, and discusses the design of hydroparks and water parks. At the end of the article are the final conclusions and concepts.